Effects of Prepolymerization, Temperature, and Hydrogen Concentration on Kinetics of Propylene Bulk Polymerization Using a Commercial Ziegler-Natta Catalyst - Huiyue Liu; Gaiping Du; Yafeng Du; Dezhan Li; Jiangbo Chen (Advances in Polymer Technology)
The effects of prepolymerization, temperature, and hydrogen concentration on propylene bulk polymerization with a commercial Ziegler-Natta catalyst were investigated, and the apparent polymerization rate constants were estimated by varying reaction temperatures, hydrogen partial pressures, and polymerization methods. It was shown that prepolymerization has different effects on the polymerization rate and isotacticity of the polymer; without prepolymerization, the polymerization rate and isotacticity reach their maximum at 70°C and 80°C, respectively, whereas the polymerization rate and isotacticity with prepolymerization increase with the polymerization temperature in the range of 50-80°C. Moderate prepolymerization time reduced the fine fraction while increasing polymerization rate and isotacticity. Appropriate prepolymerization technique can increase mass transfer performance and fragmentation, which is a promising way to improve polymerization rate, isotacticity index, and fine fraction. Otherwise, insufficient prepolymerization or excessive prepolymerization causes prepolymer particle fragmentation.